TITIK TETAP INVERS TRANSFORMASI BILINEAR DAN TRANSFORMASI BILINEAR KONJUGAT - Ansar, Ahmad (PATTIMURA UNIVERSITY, 2020)
Bilinear transformation is one of the basic transformations studied in complex function analysis and it has many applications in various fields. This article discusses about the fixed point of bilinear transformation and its properties. The results obtained are used to investigating the fixed point invers bilinear transformation. This article also explains the fixed point of the conjugate bilinear transformation.